Upaya Meningkatkan Motorik Halus Anak Usia 5-6 Tahun melalui Kegiatan Mengepang (Lidi Pelepah Sawit) di TK Tunas Harapan Desa Kuntu Kecamatan Kampar Kiri Kabupaten Kampar - Marias Marias; Susi Herlinda; Suparmi Suparmi (Darul Yasin Al Sys, 2026)
Fine motor development is an important aspect of early childhood development because it contributes to hand–eye coordination. However, preliminary observations at TK Tunas Harapan Kuntu, Kampar Kiri Subdistrict, Kampar Regency, showed that the fine motor skills of most children aged 5–6 years had not developed optimally due to the limited variety of instructional media and teaching methods used by teachers. This study aimed to improve children’s fine motor skills through braiding activities using natural materials in the form of oil palm frond sticks. The study employed a classroom action research method using a cyclical model that included the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 15 Group B children aged 5–6 years. Data were collected through observation and documentation and were analyzed using quantitative descriptive techniques with percentages. The results showed that the children’s fine motor skills improved gradually, from 47.46% in Cycle I, Meeting I to 65.62% in Cycle I, Meeting II, then increasing to 71.00% in Cycle II, Meeting I, and reaching 81.17% in Cycle II, Meeting II. These results exceeded the predetermined success indicator of 80%, indicating that braiding activities using oil palm frond sticks were effective in improving the fine motor skills of children aged 5–6 years. This study implies that the use of natural materials as learning media can serve as an effective, economical, and enjoyable alternative for supporting the development of fine motor skills in early childhood.